TRAFFIC IMPACT ANALYSIS KAWASAN `ISTANA PASTEUR REGENCY` : CASE STUDY JALAN GUNUNG BATU BANDUNG - Zulkarnaen, Dody
ABSTRACT: Along with the development of industrial architecture, a phenomenon between transportations and land development that causes changes in the land use and transportation performance is formed. The purpose of this research is to assess traffic performance of do-nothing and do-something conditions at streets and junctions around the study area. In the do-nothing condition, traffic performance is assessed with and without the influence of Istana Pasteur Regency area. The solutions for the occurring problems were also proposed. Identification of problems occurring in the study area are junction conflicts at morning and evening peak hours, while at road links, the traffic performance is stable. These problem were seen visually as well as by calculations which were shown by high degree of saturation (DS) and delay at certain junctions. The worst problems were at S3, S4, and S5 junctions. From the 3 (three) scenarios investigated, the best one is the 3rd scenario, which is the combination of the 1st and 2nd scenarios, which are, changing the circulation of traffic movement, improving the approach geometric, and installment of traffic light addition with coordinated system. The 3rd scenario, which changes unsignalized junction to signalized junction gives better junction performance. For example at S3 junction before the application of this scenario, DS = 0,70 (morning) and 0,73 (evening) decrease to 0,68 (morning) and 0,66 (evening), at S4 junction DS = 1,08 (morning) and 0,98 (evening) decrease to 0,69 (morning) and 0,72 (evening), and at S5 junction DS = 1,16 (morning) and 0,86 (evening) decrease to 0,53 (morning) and 0,70 (evening). More over delays at S3 junction 11,39 sec/smp (morning) and 11,72 sec/smp of delay (evening) decrease to 5,68 sec/smp of delay (morning) and 6,16 sec/smp (evening), delays at S4 junction 15,03 sec/smp (morning) and 14,02 sec/smp (evening) decrease to 5,58 sec/smp (morning) and 7,67 sec/smp (evening); and delays at S5 junction 5,74 sec/smp (morning) and 12,81 sec/smp (evening) decrease to 5,46 sec/smp (morning) and 5,76 sec/smp (evening).